Celebrating 20 years of the UK Dermatology Clinical Trials Network. Part 1: Developing and delivering high‐quality independent clinical trials. (1st June 2022) - Williams, Hywel C.; McPhee, Margaret J.; Layfield, Carron P.; ,; Jones, Stephen; Layfield, Carron; Matin, Rubeta; Levell, Nick; Cowdell, Fiona; Burton, Tim; Adams, Louisa May; Frankel, Jez; et al.
Summary: The UK Dermatology Clinical Trials Network (UK DCTN) was formed in 2002 with the aim of developing and supporting high‐quality independent national clinical trials that address prioritized research questions for people with skin disease. Its philosophy is to democratize UK dermatological clinical research and to tackle important clinical questions that industry has no incentive to answer. The network also plays a key role in training and capacity development. Its membership of over 1000 individuals includes dermatology consultants, trainees, dermatology nurses, general practitioners, methodologists and patients. Its organizational structures are lean and include a co‐ordinating team based at the Centre of Evidence‐Based Dermatology in Nottingham, and an executive with independent members to ensure probity and business progression. A prioritization panel and steering group enable a pipeline of projects to be prioritized and refined for external funding from independent sources. The UK DCTN has supported and completed 12 national clinical trials, attracting investment of over £15 million into UK clinical dermatology research. Trials have covered a range of interventions from drugs such as doxycycline (BLISTER), silk clothing for eczema (CLOTHES) and surgical interventions for hidradenitis suppurativa (THESEUS). Trial results are published in prestigious journals and have global impact. Genuine partnership with patients and carers has been a strong feature of the network since its inception. The UK DCTN is proud of its first 20 years of collaborative work, and aims to remain at the forefront of independent dermatological health technology assessment, as well as expanding into areas including diagnostics, artificial intelligence, efficient studies and innovative designs. Abstract : The UK Dermatology Clinical Trials Network (UK DCTN) was formed in 2002 with the aim of developing and supporting high‐quality independent national clinical trials that address prioritized research questions for people with skin disease. The figure shows the UK DCTN infrastructure.